REPRESENTASI MAKNA VERBAL DAN FUNGSI DALAM PEPATAH BAHASA KAILI DIALEK RAI DI SULAWESI TENGAH - Ulinsa Ulinsa (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2020)
The formulation of the problem in this study, namely (1) what verbal meanings are represented in the proverb in the Kaili language, Rai dialect? and (2) what function is represented in the proverb of Kaili in the Rai dialect? The research objectives, namely (1) to describe the representation of verbal meanings in the proverbial Kaili language in the Rai dialect and (2) to describe the functions represented in the proverb in the Kaili language in the Rai dialect. This type of research is qualitative with the method used is descriptive. The research was conducted in Tondo Village, Sirenja District, Donggala Regency, Central Sulawesi Province. The data source is in the form of oral sources (determining the informant). Data collection techniques in this study used field research techniques, namely observation, interviews, recording and recording. The data analysis technique is done by; collect data, reduce data, present data, and conclude. The results showed that in the proverb of the ethnic Kaili, the amount of 16 represented two forms of meaning, namely denotative meaning and connotative meaning.